Babesia spp. and Ehrlichia chaffeensis infection in Dogs from Southeastern Bahia, Brazil - Harvey, Tatiani Vitor; Veloso, Jéssica Fontes; Santos, Milane Ribeiro; Assunção, Maíra Siles; Sauer, Leonardo; Guedes, Paula Elisa Brandão; Oliveira, Thais Nascimento de Andrade; Albuquerque, George Rego; Silva, Fabiana Lessa; Munhoz, Alexandre Dias; Carlos, Renata Santiago Alberto (Acta Scientiae Veterinariae, 2017)
Background: Tickborne diseases are frequent in tropical countries such as Brazil. Protozoa of the Babesia genus and bacteria of the Ehrlichia genus spread throughout the country with high prevalences in urban and rural areas, causing clinical or subclinical diseases in dogs. This study aimed to investigate the prevalence of infection from Babesia spp. and Ehrlichia chaffeensis in the dog population in the municipality of Ituberá, Bahia, Brazil, and to verify the risk factors associated with the infections. Materials, Methods & Results: A cross-sectional study was conducted, consisting of the following procedures: clinical examination and blood samples collection from 380 dogs and application of a structure questionnaire to dog owners to collect epidemiological data. All dogs were evaluated for the presence of ticks and clinical signs associated with the infections. Blood samples were collected and tested for Babesia spp. through capillary blood smears, indirect immunofluorescence assays (IFAT), and polymerase chain reaction (PCR); all the samples were also tested for E. chaffeensis through nested PCR. Intra-erythrocyte piroplasms were visualized in the blood smears of two animals (2/380; 0.5%) in the cytology exams. Anti-B. canis antibodies were detected in 140/380 (36.8%) dogs, at 1:40 dilution. By PCR, 147/380 (38.7%) dogs tested positive for infection by Babesia sp., but no animal was infected by E. chaffeensis. Only 115/380 dogs (30.3%) were infested by ticks. In total, 223/380 dogs (58.7%) were found infected by Babesia spp. No clinical signs were it found to be significant for the infection. The infected (Ht = 40%) and uninfected dogs’ (Ht = 39%) hematocrit averages were not found to significantly differ (P = 0.47). No hematological changes were found to be significant for the disease. The evaluated variables sex, habitat (urban or rural), exposure to other dogs, age, and infestation by ticks were not found to be risk factors. The condition of semirestriction of 175/223 (78.4%) dogs was found as a risk factor for the infection (P = 0.01; OR = 1.75; IC 95% = 1.10-2.78). Discussion: The low detection from blood smears was inferior to the lowest prevalences found in Brazil. On the other hand, the high seroprevalence rate by IFAT observed in this study was found in other Brazilian states. The low infection prevalence in the cytologic analysis associated with high seroprevalence are characteristics of chronic or subclinical infections. The high seroprevalence rates may also indicate chronicity and/or subclinical disease when associated with low parasitemia and may also be indicated by the low title variation observed. In this study, some dogs that tested positive for Babesia by serology tested negative in the PCR, which suggests a previously exposure to this pathogen and maintenance of detectable levels of antibodies, or that they were subclinical or chronic carriers of the infection. The equal hematocrit averages of dogs either carrying or not the disease suggests that the infected animals, especially the seemingly healthy dogs, are subclinical or chronic carriers, either asymptomatic or otherwise, that are adapted to the disease, which may contribute to the agent remaining in this population. The fact that no clinical sign of hematological change was significant for the infection may demonstrate the low pathogenicity of this agent in the evaluated population. The semi-restricted condition of the dogs as a risk factor is probably due to the increased exposure of these animals to canine babesiosis vectors during their movement through different neighborhood areas and villages in the municipality. The combination of diagnostic methods is important to identify the infection and determine its prevalence in epidemiological studies. Also, PCR was fundamental in this study, to identify the infection in asymptomatic dogs.